2021
DOI: 10.3390/antibiotics10060654
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiogram of Vibrio parahaemolyticus and Aeromonas hydrophila in the Flesh of Nile Tilapia, with Special Reference to Their Virulence Genes Detected Using Multiplex PCR Technique

Abstract: Vibrio parahaemolyticus and Aeromonas hydrophila are major public health problems and the main cause of bacterial disease in Nile tilapia (Oreochromis niloticus). This study was conducted to determine the prevalence, antibiotic resistance and some virulence genes of both V. parahaemolyticus and A. hydrophila isolates from Nile tilapia. From Manzala Farm at Dakahlia governorate, 250 freshwater fish samples were collected. The confirmed bacterial isolates from the examined Nile tilapia samples in the study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Tilapia may be infected with various bacteria, including species of the genera Vibrio , Aeromonas , Pseudomonas and Streptococcus , 5 whereas some genera may be present also on healthy fish, like species of the genera Pseudomonas Aeromonas , and Plesiomonas 6 . In general, most fish diseases are induced by a stress factor, like a suboptimal environment, for instance, bad water quality, and this allows opportunistic bacteria including Aeromonas hydrophila to infect tilapia and cause disease 7–9 . Moreover, many bacterial diseases are multifactorial 10 .…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tilapia may be infected with various bacteria, including species of the genera Vibrio , Aeromonas , Pseudomonas and Streptococcus , 5 whereas some genera may be present also on healthy fish, like species of the genera Pseudomonas Aeromonas , and Plesiomonas 6 . In general, most fish diseases are induced by a stress factor, like a suboptimal environment, for instance, bad water quality, and this allows opportunistic bacteria including Aeromonas hydrophila to infect tilapia and cause disease 7–9 . Moreover, many bacterial diseases are multifactorial 10 .…”
Section: Reviewmentioning
confidence: 99%
“…Nile tilapia juveniles, after being exposed to transport‐induced stress, appeared to have 19 responsible isolates of A . hydrophila in their body, as identified by 16S rRNA testing 9 . The A .…”
Section: Reviewmentioning
confidence: 99%
“…The third study from Egypt (Zaher et al, 2021 ) was also based on disk diffusion but provided a reference with a non‐standard method for the medium and temperature (30°C), and then classified isolates as sensitive, intermediate and resistant according to a breakpoint designed for a different media and temperature (35°C). Hence, results should also be interpreted with care, as highlighted by the surprisingly low levels of resistance found for ampicillin among the 19 isolates tested (52.6%, with 32% of the remaining isolates classified as intermediate).…”
Section: Assessmentmentioning
confidence: 99%
“…As described above, three references (Lukkana et al, 2012 ; Scarano et al, 2018 ; Zaher et al, 2021 ) reported different proportions of susceptible isolates to amoxicillin and/or ampicillin in their bacterial panels, even though mesophilic Aeromonads are considered intrinsically resistant to aminopenicillins (CLSI, 2016 ), thus highlighting the difficulties associated with the evaluation of the resistance phenotype in A . hydrophila isolates (and in bacteria from aquatic animals in general), a process in which small variations may lead to significant variations in the results.…”
Section: Assessmentmentioning
confidence: 99%
“…Although V. parahaemolyticus infection has been commonly associated with seafood consumption, its existence in non‐seafood products such as freshwater fish and infections caused by contaminated non‐seafood products have also been reported (Chao et al, 2009; Liu et al, 2015). Zaher et al reported a prevalence rate of 24.8% (62/250) for Nile tilapia samples (Zaher et al, 2021) and Li et al found that 3.67% of 300 miscellaneous ready‐to‐eat food samples were positive for V. parahaemolyticus (Li et al, 2020). Dong et al isolated and characterized V. parahaemolyticus strains from crayfish raised in freshwater (Dong et al, 2016) and a V. parahaemolyticus outbreak with 375 infections were attributed to undercooked frozen crayfish in Jiangxi province, China in 2011 (Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%